Sign of the Raven - Hearn, Julie, 1958- (Atheneum Books for Young Readers, 2005)
In the basement of his grandmother's home in London where his mother is recuperating from cancer, twelve-year-old Tom discovers a path to the past where, in the year 1717, a "fairy child" and her friends desperately need his help.